Fuzzy Non-Linear Programming Problems with Linear Inequality Constraints and Its Solutions - Purnima Raj, Ranjana (Mathematical Statistician and Engineering Applications, 2021)
The problem of “fuzzy nonlinear programming is useful for solving problems that are difficult, impossible to solve because of the inaccurate and subjective nature of the problem formulation, or that have a precise solution. We have an objective function here that we have to optimize with certain constraints. This document proposed finding the fuzzy solution to totally fuzzy nonlinear programming problems with inequality constraints using the proposed method, the fuzzy solution to the FFNLP problems with inequality constraints that occur in real-life situations (Loganathan and Lalitha 2017). Fuzzy numbers are known to be the coefficients of nonlinear objective functions and constraints. Numerical examples were illustrated of the method. A new method for finding an optimal solution to fuzzy, nonlinear programming problems is proposed here in this document. Various authors have proposed algorithms which include problems with linear programming with linear constraints.” The method proposed is based on previous works available in the literature and is checked by numerical examples.